IMF Survey, Volume 36 Issue 08. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
De Rato on hedge funds and trade; Portugal on IMF technical assistance; Latin American growth; Iraq reforms economy; debt restructuring in eight countries; IMF research: investment, reserves, inflation; exchange rate adjustment and global imbalances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet